Eficacia farmacológica en pacientes con sobrepeso y obesidad atendidos en la consulta endocrinológica del Hospital-Universidad Técnica Particular de Loja - Ramón Gordillo, Ana Gabriela (2023)
Obesity and overweight represent a health problem, predisposing to the development of nontransmissible diseases. The research had as a purpose to classify the patients with overweight and obesity and establish the relation according to their age group, sex, lipid and triglyceride levels; blood pressure, glucose and habits; before and after the drug treatment with phentermine and topiramate, in the endocrinological particular clinic of the Universidad Técnica Particular de Loja. It has a quantitative and longitudinal approach, a sample of 24 patients and the use of body mass index, The Adult Treatment Panel III Guidelines, 2018 European arterial hypertension Guide, 2021 American Diabetes Guide, International physical activity Test, Audit Test, reduced Fagerström Test and 24 hour Reminder. Obtaining before the treatment 80% of men who presented grade II obesity and 60% of prediabetes values for fasting glucose; 36.84% (n=7) of women were overweight, accompanied by low physical activity and excessive consumption of calories for both groups. After treatment, women showed a greater decrease in body mass index from overweight to normal 15.79% (n=3), with an increase in blood pressure from optimal to normal 52.63% (n=10), accompanied by low physical activity and calories deficit for both groups. Determining the relationship by calculating the Chi square, there is a statistically significant relationship with a value of p<0.05, concluding the efficacy of the pharmacological treatment associated with the lifestyle of overweight and obese patients